Influence of Brand Personality on Purchase Decisions: A Case Study of Nike Shoes in Ambon City - Merry Pelupessy; Erlinda Tehuayo (International Journal of Community Service & Engagement, 2021)
The purpose of the study was to analyze the influence of brand personality on purchasing decision for Nile shoes in the city of Ambon. this research is a descriptive research. The population in this study are users of nike  shoes in Ambon city. And The Number Of Sampel Is 100 respondents.By using a questionnaire as a data collection tool. Taking the sample using non probability sampling with the data analysis method used is multiple linear regression. Based on the results of multiple linear regression test that the brand personality variable has a positive and significant effect on the decision of 0,396 which means that the brand personality variable is considered important when consumers will make a decision to buy nike shoes.